Education in a Diverse Society Necessitates the Implementation of an Equitable Language Policy: The Russian Experience. Issue 1 (January 2013) - Sinagatullin, Ilghiz M.
Russia's secondary school populations are becoming increasingly diverse in terms of ethnicity, culture, language, and religion. The growing diversity makes a considerable impact on the functions and goals of schools, the realization of which requires the implementation of an equitable language policy. In this article, I briefly represent Russia as a diverse society, examine a range of important functions of the secondary school, introduce the language situation being unfolded on a nationwide scale, and capture the essentials of a language policy that young graduates need to productively function in their own community, the mainstream society, and in an interdependent global space.